2022
DOI: 10.3389/fpsyg.2022.1011095
|View full text |Cite
|
Sign up to set email alerts
|

Early-childhood temperament moderates the prospective associations of coping with adolescent internalizing and externalizing symptoms

Abstract: While appraisal and coping are known to impact adolescent psychopathology, more vulnerable or resilient responses to stress may depend on individual temperament. This study examined early life temperament as a moderator of the prospective relations of pre-adolescent appraisal and coping with adolescent psychopathology. The sample included 226 (62% female, 14–15 years) adolescents with assessments starting at 3 years of age. Adolescents were predominately White (12% Black 9% Asian, 11% Latinx, 4% Multiracial, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…However, only a handful of studies included in our systematic review conducted multiple COVID-19 follow-ups and employed a study design that could answer such an important question. For instance, Smith et al (2022) assessed pandemic outcomes at two intervals eight months apart, and found that whilst pre-pandemic coping abilities had no impact on psychopathology during the initial outbreak, they were associated with decreased internalising symptoms as time progressed. Bussone et al (2023) reported similar findings, however, their study lacked methodological robustness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a handful of studies included in our systematic review conducted multiple COVID-19 follow-ups and employed a study design that could answer such an important question. For instance, Smith et al (2022) assessed pandemic outcomes at two intervals eight months apart, and found that whilst pre-pandemic coping abilities had no impact on psychopathology during the initial outbreak, they were associated with decreased internalising symptoms as time progressed. Bussone et al (2023) reported similar findings, however, their study lacked methodological robustness.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Holt-Gosselin et al (2022) found no association between pre-pandemic adaptive coping and pandemic depression or anxiety symptoms in a sample of young adults. Smith et al (2022), however, assessed pandemic outcomes at two intervals eight months apart, and found that whilst pre-pandemic coping abilities had no impact on psychopathology during the initial outbreak, they were associated with decreased internalising symptoms as time progressed. Bussone et al (2023) identified a comparable trend, although focusing on a different aspect of resilience.…”
Section: Individual Factorsmentioning
confidence: 99%